Distribución espacial de la conductividad hídrica en el campus CEASA - Curay Changoluisa, Jimena Verónica (2018)
The study of the spatial distribution of water conductivity was conducted at the Technical University of Cotopaxi in the Campus Salache: This tool is displayed as an important part to counteract the environmental effect, soil erosion by runoff from imbalance infiltration Was raised to generate a model for conductivity spatial sampling, sampling points are designed and places them in the field. The digital modeling it performed in the ArcGIS software Versíon 10.2.2. the amount of water conductivity is determined and place isolines conductivity is performed. With the information a map with 24 sampling points spread over 12,000 m2 is dimensioned. The determination of conductivity to identify that the rate is moderate basic infiltration average values of 24. 49 mm / h with soil type clay loam, sandy loam changing. The development of hydraulic conductivity isolines identifies modeled in a graphical zones of the study area with major and minor infiltration and conductivity. Isolines development is a graphical way of modeling the conductivity having a floor spatially, meeting all requirements according to technical rules easy to interpret and meets the needs of the study.